Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The Effectiveness of Using Dual Situated Learning Model (DSLM) to Teach Physics in the Development of Conceptual Comprehension of Secondary School Male StudentsDr. Abdulaziz Mohammed Hamdi2. Positive personality traits and their impact on positive organizational behavior in the work environment A field study on the staff of some faculties of Alasmarya Islamic UniversityCo-Prof. Ayada Masoad Agob, Co-Prof. Rabia Omar Lahderi3. The Reality of Applied the Global Entrepreneurial In Jordanian UniversitiesDr. Mohammed Saleh Al-Ajami4. The impact of employing some applications of the second generation of the Web (WEB2.0) on the marketing and development of learning resource center servicesMr. Ali Salim Mohammed Albalushi5. The role of field training in improving cognitive development and building personality among psychological counseling students at Al Alsharqiyah University in the Sultanate of OmanDr. Khulood Ahmed Amur Al-Obaidani6. Modern Methods for Learning Outcomes Evaluation in Educational Institutions: Theoretical InvestigationMrs. Huda Abdullah Al-Zahrani7. Research Status and Trends in the Flipped Classroom Model for Learning with Technology: A Systematic Review of Peer-reviewed Empirical Studies Published in Different Journals up to 2022Dr. Hanaa Eid Alharbi
Keywords: Journal of Educational and Psychological Sciences